2014
DOI: 10.1016/j.stemcr.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Human Migratory Meniscus Progenitor Cells Are Controlled via the TGF-β Pathway

Abstract: SummaryDegeneration of the knee joint during osteoarthritis often begins with meniscal lesions. Meniscectomy, previously performed extensively after meniscal injury, is now obsolete because of the inevitable osteoarthritis that occurs following this procedure. Clinically, meniscus self-renewal is well documented as long as the outer, vascularized meniscal ring remains intact. In contrast, regeneration of the inner, avascular meniscus does not occur. Here, we show that cartilage tissue harvested from the avascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 42 publications
4
64
0
3
Order By: Relevance
“…Identification of CD166-positive cells in the surface layers of the meniscus in our current study is consistent with previous reports indicating the presence of stem or progenitor cells in this area (2325). The expression of CD166 suggests that these cells could be progenitors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Identification of CD166-positive cells in the surface layers of the meniscus in our current study is consistent with previous reports indicating the presence of stem or progenitor cells in this area (2325). The expression of CD166 suggests that these cells could be progenitors.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of progenitor cells would appear to be in conflict with the capacity of the avascular region to self-heal (1416). Meniscus progenitors in normal meniscal tissue are likely quiescent, but cells positive for several stem cell markers including CD105, CD106 and STRO-1 emerge from and migrate into diseased or disrupted tissues (25). Although the inner bulk tissue of the avascular region lacked identifiable progenitor populations, the presence of progenitors on the surface of the meniscus opens the possibility of developing methods to better characterize, stimulate, and utilize these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanderploeg et al [6] showed collagen type VI to be concentrated in inner meniscal regions and localized to the pericellular matrix; in this study, omECM supplementation downregulated Col6 expression, as compared with Controls and imECM constructs. In examining additional putative meniscal cell markers [31], ECM supplementation tended to have a negligible or inhibitory effect at early time points, with broad equivalency across groups by day 42. The extent that these transcriptional changes are meaningful for tissue engineering application remains uncertain, given the paucity of studies characterizing the phenotypes of cells across various meniscus regions.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of these progenitor cells was first proposed by Hayes et al on the basis of their observation that cartilage exhibits appositional growth during development. 20 Mesenchymal progenitor cells have been found in many areas of the joint, including cartilage, synovial lining, bone marrow, infrapatellar fat pad, meniscus, and even tendons, [21][22][23][24][25][26][27][28][29] and it has been proposed that they may be quiescent remnant cells from the developing limb bud mesenchyme. 30 Cartilage-derived mesenchymal progenitors make up a small percentage of all cells in the cartilage tissue 31 and reside side-by-side with the more abundant chondrocytes throughout cartilage; however, they are most abundantly found in the superficial zone, specifically in the articular surface.…”
Section: Local Stem/progenitor Cellsmentioning
confidence: 99%